Fostering an intimate interplay between research and practice: Danish ”maths counsellors” for upper secondary school - Jankvist, Uffe Thomas; Niss, Mogens (NOMAD Nordic Studies in Mathematics Education, 2020)
The gap between research and practice is a well-known problem (and topic) in educational research, and not least in mathematics education research. This empirically based article discusses the effects of a particular attempt to foster a closer connection between research and practice by involving mathematics education research findings in the activities of selected Danish upper secondary school mathematics teachers, who (have) take(n) part in a research-based so-called ”maths counsellors” in-service teacher programme. A key aspect of the programme is to make the activation of research findings a mere necessity for significant aspects of the maths counsellors’ practice. To illustrate the teachers’ research-based work, the article presents six characteristic examples from the implementation of the programme, i.e. authentic examples of how prospective maths counsellors have identified students with mathematics specific learning difficulties, have diagnosed the nature of these difficulties, and how they have designed interventions to help the students overcome them. A discussion of how these activities draw upon and are grounded in mathematics education research findings serve as a basis for evaluating the ”model” behind this further education programme.